If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+2-3x+3=x-9
We move all terms to the left:
6x+2-3x+3-(x-9)=0
We add all the numbers together, and all the variables
3x-(x-9)+5=0
We get rid of parentheses
3x-x+9+5=0
We add all the numbers together, and all the variables
2x+14=0
We move all terms containing x to the left, all other terms to the right
2x=-14
x=-14/2
x=-7
| 8/p=-96 | | (5+u)(4u+6)=0 | | x9=x5 | | 1/4d+8=12 | | 24=2(y+6)-8y | | 3y+6+y=4y-1+9 | | 12=4w+4(w-5) | | 1.7/n=4.59 | | 3y+6+y=4y- | | -6x+3(x+7)=15 | | -4j+17=1 | | -6x+3(x+17)=15 | | 5x+6=6x-15 | | 4(u-3)+7u=10 | | 336=8(8a-6) | | 3j=8+4j | | x3-4=-19 | | -6(y-2)=24 | | 4x(5+6)=4 | | x2-34x+145=0 | | 330=6(8a-1) | | 3x-13+2x+12=180 | | x2+34x+145=0 | | -6x+9x-10=-28 | | (2x)+(x200+(x135)=1735 | | 5x-1)+39=90 | | x-1/3*5=2x | | 41+k=27 | | (5x-10)+39=90 | | 3x−23+2x−12=180 | | 2y-6-5y=-3y-9 | | -2y+14=3/ |